Homeopathic Management of an Acute uncomplicated Urinary Tract Infection with Cystitis without Antibiotics in a Child- A Case Report (Advancements in Homeopathic Research, 2022)
Background -Cystitisis the medical term for inflammation of the bladder. Most of the time, the inflammation is caused by a bacterial infection, and it’s called a urinary tract infection. A bladder infection can be painful and annoying, and it can become a serious health problem if the infection spreads to your kidneys.The usual treatment for bacterial cystitis is antibiotics. Treatment for other types of cystitis depends on the underlying cause. Method-A single acute clinical case of urinary tract infection with cystitis in a child was treated with an individualised homeopathic treatment, without aid of antibiotics. Urine routine and microscopic test pre and post homeopathic treatment were used for assessment of the case. Result-the patient recovered remarkably with Homeopathic therapy. Interpretation-Homeopathy is rapid in treating pyuria in a child without antibiotics. Conclusion-Homeopathic therapy was observed to treat the urinary tract infection with cystitis in a child, which is routinely treated with antibiotics, with a rapid and a gentle approach .
Keywords: Homeopathic Management; Cystitisis; bladder infection